Negro family in the United States - Frazier, E. Franklin; Gla , Nat (Fwd.) (Chicago, 1939)
In his preface to The Negro Family in the United States, on its first publi cation, Ernest W. Burgess called it "the most valuable contribution to the literature of the family since the publication, twenty years ago, of The Polish Peasant in Europe and America." The passage of twenty-seven years has in no way reduced the stature of this classic work; on the contrary, viewing it now in the new contexts of the Negro revolution and the convulsive response to it of American society and government, we must give Frazier's study even higher praise than Burgess gave it. Written during American sociology's only golden age, it is to my mind. one of the most substantial and enduring works of that age. Ironically, many efforts to establish a timeless theoretical framework for sociology and social analysis now appear to us dated and remote. This book, con cretely based on the realities of Negro family life, reconstructed eclecti cally from personal accounts, literature, statistics and observation and direct experience, has lost nothing in immediacy and relevance.
Keywords: Sociology